The Satisfaction of Copy Denture Box for Replica Denture Procedures - Norlela Yacob; Khaliesah Abdul Rahim; Mohd Nazrin Mohd Isa; Faizah Abdul Fatah (Universiti Sains Islam Malaysia, 2024)
Replica denture procedure is one of the technique for replacement of the old complete. The objective of this study was to assess the satisfaction of copy Denture Box in the mode of easy-handling, cost effectiveness and time saving. Seven prototypes of Denture Box were constructed using 3D printer using ABS materials. 30 dental technicians had been randomly selected from three public universities and private dental laboratory. The respondents were given a chance to try the Denture Box using alginate to produce a mould for making the replica. A pre-tested questionnaire consisted of few questions pertaining knowledge, background and satisfaction towards the copy Denture Box were distributed. 15 (n) respondents had tried the Denture box. Most of the respondent has 10-15 years of working experience. 87% (n=13) respondents were agreed that the copy denture box was easy to handle with a mean score of 4.13((± 0.25) and able to save cost, 93% (n=14) with a mean score of 3.93 ((±0.18). Even though all the respondents were satisfied with the box, there was no statistical relationship between subjects preference technique and their willingness to use the newly invented box in the future (p>0.05). Respondents gave an encouraging feedback in the manner of easy-handling, cost effectiveness and time saving of the copy Denture Box. Further study to assess the accuracy of the replica is recommended.